Delaying the bell: the effects of longer school days on adolescent motherhood in Chile - Diana I. Kruger; Matias E. Berthelon (Institute for the Study of Labor (IZA), 2009)
We analyze the effect of a Chilean school reform that lengthened the school day from half to full-day shifts on the likelihood that adolescent girls become mothers. By increasing the number of hours spent in school, the reform curtails opportunities to engage in risky sexual behaviors. Using Chile's socio-economic household surveys and administrative data from the Ministry of Education from 19902006, we exploit the exogenous time and regional variation in the implementation of the reform to identify the effects of increased education and adult supervision on the likelihood that adolescent girls become mothers. We find that access to full-day schools reduces the probability of becoming an adolescent mother among poor families and in urban areas: an increase in full-day municipal enrollment of 20% reduces the likelihood of teen motherhood by 5%.
Keywords: H51; I18; I28; J13; O15; 330; Adolescent motherhood; adolescent pregnancy; school day reform; Chile; Bildungsreform; Jugendliche; Schwangerschaft; Mütter; Bildungsverhalten; Chile